Effect of Chitosan Elicitor Addition and Elicitation Duration on the Growth and Antioxidant Activity of Shallot (Allium ascalonicum L.) Callus - Muhyidin, Faricha Aulia; Habibah, Noor Aini (El-Hayah:Jurnal Biologi, 2025)
Shallot (Allium ascalonicum L.) contains various active secondary metabolites such as phenolics, flavonoids, quercetin, saponins, and anthocyanins, which function as natural antioxidants to protect the body from free radicals. Callus culture with the addition of elicitors is an effective method to produce shallot callus with enhanced secondary metabolite content compared to the original plant through manipulation of biosynthetic pathways. This study aimed to determine the most optimal combination of chitosan concentration and elicitation duration to enhance the growth and antioxidant activity of shallot bulb callus in vitro. A Completely Randomized Design (CRD) was used with 12 treatment combinations (chitosan at 50, 100, 150, and 200 mg/L for 2, 4, and 6 days) and 1 control treatment. The results showed that the elicitation combination had no significant effect on fresh weight but significantly affected dry weight and antioxidant activity of the callus. The control treatment was the most optimal for callus growth, yielding the highest average biomass (0.07 grams). Meanwhile, the 2 days + 200 mg/L combination treatment was the most optimal for increasing the antioxidant activity of the callus, producing the highest inhibition value (35.65%). Callus morphology in all treatments exhibited compact texture and varied shades of yellow. This study demonstrates that chitosan elicitor is effective in enhancing the antioxidant activity of A. ascalonicum callus and is therefore recommended for further phytochemical and biotechnological development.